Comparative Studies on the Susceptibility of (R)-2,3-Dipalmitoyloxypropylphosphonocholine (DPPnC) and Its Phospholipid Analogues to the Hydrolysis or Ethanolysis Catalyzed by Selected Lipases and Phospholipases - Paweł Mituła; Czesław Wawrzeńczyk; Witold Gładkowski (Catalysts, 2021)
Susceptibility of soybean phosphatidylcholine, 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) and its phosphono analogue (R)-2,3-dipalmitoyloxypropylphosphonocholine (DPPnC) towards selected lipases and phospholipases was compared. The ethanolysis of substrates at sn-1 position was carried out by lipase from Mucor miehei (Lipozyme®) and lipase B from Candida antarctica (Novozym 435) in 95% ethanol at 30 °C, and the hydrolysis with LecitaseTM Ultra was carried out in hexane/water at 50 °C. Hydrolysis at sn-2 position was carried out in isooctane/Tris-HCl/AOT system at 40 °C using phospholipase A2 (PLA2) from porcine pancreas and PLA2 from bovine pancreas or 25 °C using PLA2 from bee venom. Hydrolysis in the polar part of the studied compounds was carried out at 30 °C in acetate buffer/ethyl acetate system using phospholipase D (PLD) from Streptococcus sp. and PLD from white cabbage or in Tris-HCl buffer/methylene chloride system at 35 °C using PLD from Streptomyces chromofuscus. The results showed that the presence of C-P bond between glycerol and phosphoric acid residue in DPPnC increases the rate of enzymatic hydrolysis or ethanolysis of ester bonds at the sn-1 and sn-2 position and decreases the rate of hydrolysis in the polar head of the molecule. The most significant changes in the reaction rates were observed for reaction with PLD from Streptococcus sp. and PLD from Streptomyces chromofuscus that hydrolyzed DPPnC approximately two times slower than DPPC and soybean PC. The lower susceptibility of DPPnC towards enzymatic hydrolysis by phospholipases D gives hope for the possibility of using DPPnC-like phosphonolipids as the carriers of bioactive molecules that, instead of choline, can be bounded with diacylpropylphosphonic acids (DPPnA).